An innovative biochar-amended substrate vertical flow constructed wetland for low C/N wastewater treatment: Impact of influent strengths. (January 2018) - Zhou, Xu; Liang, Chenglong; Jia, Lixia; Feng, Likui; Wang, Ruigang; Wu, Haiming
Graphical abstract: Highlights: Biochar addition in VFCWs enhanced pollutant removal from low C/N wastewater. Higher removal rate was obtained in biochar-VFCWs even at high influent strength. Biochar-VFCW is useful for N2 O emission reduction at various influent strengths. Abstract: Application of biochar can be an effective and low cost technique for wastewater treatment while reducing greenhouse gas emissions. In this study, biochar was used as substrates in Vertical flow constructed wetlands (VFCWs) for enhancing the removal of contaminant from low C/N wastewaters with different influent strengths. The removal of organic matter and nitrogen in biochar-added and non-biochar-added VFCWs with different low C/N influent strengths were evaluated systematically. The results demonstrated that combining VFCWs and biochar addition could be an appropriate strategy as compared to conventional VFCWs with average removal of organic pollutants (85%), NH4 + -N (39%) and TN (39%) especially at high influent strengths. Meanwhile, N2 O emission was also significantly lower in biochar-added VFCWs (138–1008 μg m −2 h −1 ) than that in non-biochar-added VFCWs (164–1304 μg m −2 h −1 ) under different influent strengths. We believe that VFCWs by adding biochar can be a useful technology for treating low C/N wastewaters.